Modelling and simulation of drying process for ceramic membrane fabrication - Ong, Tze Ching (2015)
For ages, ceramic properties and structure is known for its brittleness and its failure such as cracking and warping. This weakness also relates to the high sensitivity of ceramic to any thermal gradient effects. Therefore, processing steps of green body of ceramic is crucial especially in membrane fabrication that has a multilayer structure to ensure the efficiency of its applications. Thus, every step of ceramic membrane preparation and fabrication needs careful control and monitoring to fulfil these aims. Drying is one of the main problems that is always associated with the cracks and leakages of the ceramic membrane. In fact, the drying process is one of the longest steps corresponding to various evolutions of parameters during the evaporation process. Due to the limitation in experimental or empirical ability to determine the changes of dynamic critical variables during drying, modelling and simulation seems to be the right option to determine and investigate these nonlinear and dynamic variables and will be the focus of this study. This two-dimensional mathematical modelling approach is able to predict the changes of variables in heat and mass transfer during the drying process. The governing system of fully coupled non-linear partial differential equations of the model was derived from a mechanistic approach where the mass and energy conservation laws are defined for a particular phase into which Darcy’s law and Fick’s law are substituted. A fully implicit algorithm has been employed for numerical solution using the finite element method in which the Galerkin weighted residual method is used in the spatial discretization and a backward finite difference time-stepping scheme is employed for time integration. The ability of this improved model is not restricted to a single homogenous layer of hygroscopic and nonhygroscopic material, but on the novelty to incorporate multilayer heterogeneous material properties as a membrane structure. A good agreement obtained by respective validation works suggested that the model development and implementation are satisfactory. Subsequently, case studies involving single layer and multilayer have produced reasonable accuracy at all times. The application of the model at various case studies involves a convective and enhanced intermittent drying mode which demonstrates the robustness and trustworthiness in predicting and optimising the drying process.